One-Piece Titanium Implants: Retrospective Case Series - Gunar Wagner; Dieter Hartung (Case Reports in Dentistry)
Purpose. One-piece titanium implants are not routinely used for reconstruction after tooth loss. Several limitations seemed to be apparent although the concept provides a straightforward approach for different clinical situations. A clinical documentation of five prosthetic restorations with one-piece titanium implants serving as a relevant treatment option in dental surgery is pursued. We demonstrate the feasibility and benefits of one-piece titanium implants for fixed dental prosthesis. Detailed descriptions of the technical features and the surgical approach by means of clinical cases are given. The prosthetic workflow when working with one-piece titanium implants is depicted in detail as well as examples for implant-supported tooth replacement in the posterior region and the esthetic zone. Conditions of applications regarding different timing of implant placement using the system and its limitations are discussed. Results. Clinical cases with a follow-up period of up to 10 years are presented to prove the long-term success of one-piece titanium implants in terms of bone and soft-tissue stability respecting the biological criteria for periodontal health. Conclusions. One-piece titanium implants represent a reliable treatment method for single-tooth replacements. Clinical success with long-time bone stability around the implantation site can be achieved. Taken into account the requirements for periodontal tissue stability, uneventful healing without extensive tissue loss is demonstrated by means of clinical cases presenting patients with periodontitis.